Respuesta :

(x + 1)

As:

(2x + 3)(x + 1) = 2x2 + 2x + 3x + 3

= 2x2 + 5x + 3

Answer:

The missing term is [tex]1[/tex]

Step-by-step explanation:

we have

[tex]2x^{2} +5x+3[/tex]

Let

b-----> the missing term

we know that

[tex]2x^{2} +5x+3=(2x+3)(x+b)[/tex]

solve for b

[tex]2x^{2} +5x+3=(2x+3)(x+b)\\ \\2x^{2} +5x+3=2x^{2} +2xb+3x+3b\\ \\2x^{2} +5x+3=2x^{2} +x(2b+3)+3b[/tex]

Solve the system

[tex]2b+3=5[/tex] ------>[tex]b=1[/tex]

Verify in the second equation

[tex]3b=3[/tex] ------> substitute the value of b ----> [tex]3=3[/tex] --> is ok

therefore

[tex]2x^{2} +5x+3=(2x+3)(x+1)[/tex]